Strategi Guru PAI dalam Meningkatkan Partisipasi Belajar Siswa Berkemampuan Rendah di SDN 008 Tebing Karimun - Safira Laila Wulandari; Salsa Bila Ivanda; Nur Azizah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study aims to describe the strategies of Islamic Religious Education (PAI) teachers in increasing the learning participation of low-ability students at SDN 008 Tebing Karimun. Learning participation is an important indicator of learning success, but in reality there is still low student involvement in the learning process. Inhibiting factors come from internal aspects such as low confidence and limited cognitive abilities, as well as external aspects in the form of less varied learning strategies and less supportive classroom environments. This study uses a qualitative approach with a descriptive type, involving PAI teachers as the main informants and students as supporting informants. Data was collected through observation, interviews, and documentation, then analyzed with an interactive model that included data reduction, data presentation, and conclusion drawn, and tested for validity through triangulation. The results of the study showed that teachers' strategies include active learning, group discussions, individual approaches, and the use of learning media. The obstacles faced include low student confidence, cognitive limitations, and lack of variety of methods. The solutions carried out by teachers are in the form of providing motivation, applying innovative methods, and creating a conducive learning environment. This study concludes that PAI teachers' strategies play an important role in increasing the learning participation of low-ability students through innovative, interactive, and student-centered learning.